Judges, 'common sense' and judicial cognition. Issue 3 (2nd July 2016) - Burns, Kylie
ABSTRACT: Judges are like other human beings. They use their 'common sense', their common understanding, their contemporary knowledge of society and the expectations of the community, as part of judicial decision-making. Judicial common sense understandings about the world and human behaviour may also form a silent lens through which judges interpret the meaning of matters such as reasonableness and normality of human behaviour, and assess the meaning of visual phenomenon such as signs, pictures and video. However, judges may be unconsciously impacted by cognitive limitations. Judge's factual assumptions may be influenced by their own cultural worldviews. Judicial use of common sense can be the vehicle through which error and discrimination enter the law. Part 2 of this article examines how judges use common sense in their judicial reasoning. Part 3 suggests that judicial construction of common sense is a cognitive process with the consequent impact of bounded rationality, heuristics, biases, emotion and cognitive illusions. Part 4 discusses whether judges can overcome the limitations of common sense reasoning. The article argues that while common sense and common understandings will always be an inevitable part of judicial decision-making more attention is required to address the limitations of common sense judging.